2005
DOI: 10.1111/j.1600-079x.2005.00265.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial pleiotropic actions of melatonin in an experimental model of septic shock in mice: regulation of pro‐/anti‐inflammatory cytokine network, protection against oxidative damage and anti‐apoptotic effects

Abstract: Septic shock, the most severe problem of sepsis, is a lethal condition caused by the interaction of a pathogen-induced long chain of sequential intracellular events in immune cells, epithelium, endothelium, and the neuroendocrine system. The lethal effects of septic shock are associated with the production and release of numerous pro-inflammatory biochemical mediators including cytokines, nitric oxide and toxic oxygen and nitrogen radicals, together with development of massive apoptosis. As melatonin has remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
2
8

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(182 citation statements)
references
References 69 publications
7
165
2
8
Order By: Relevance
“…Many of the gene changes described here are consistent with the observations that injection of LPS is more lethal for old mice than for young (Saito et al, 2003), and that survival is increased by melatonin, at least in young animals (Carrillo-Vico et al, 2005). The issue as to how gene expression patterns may be consistent with, or in some cases contradictory to, the mortality data is now discussed.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Many of the gene changes described here are consistent with the observations that injection of LPS is more lethal for old mice than for young (Saito et al, 2003), and that survival is increased by melatonin, at least in young animals (Carrillo-Vico et al, 2005). The issue as to how gene expression patterns may be consistent with, or in some cases contradictory to, the mortality data is now discussed.…”
Section: Discussionsupporting
confidence: 73%
“…injection of LPS (Saito et al, 2003). Melatonin also increases the survival rate of young mice injected with an otherwise lethal dose of LPS (Carrillo-Vico et al, 2005). The age-related decline in amplitude of circadian melatonin secretion is especially pronounced in aged demented subjects and the decline of its nocturnal peak is correlated with the severity of cognitive impairment (Magri et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…It was demonstrated that nitric oxide (NO) plays an important role in septic shock, an acute inflammatory response [134]. Indeed, melatonin improves the survival of mice with LPS-induced shock by -11 -reducing NO synthesis via its antioxidant and anti-apoptotic properties [135]. It was demonstrated that antioxidant treatment improves respiratory syncytial virus (RSV)-induced pulmonary inflammation.…”
Section: Role Of Melatonin In Maintaining and Restoring Human Healthmentioning
confidence: 99%
“…37 In murine septic shock models, melatonin supplementation has been reported to increase survival by down-regulating pro-inflammatory cytokines and also lipid peroxidation levels in the brain. 38 …”
Section: Infection and Melatoninmentioning
confidence: 99%